2009
DOI: 10.1017/s0952523809990253
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution, contrast sensitivity, and sensitivity to defocus of chicken retinal ganglion cells in vitro

Abstract: The chicken has been extensively studied as an animal model for myopia because its eye growth is tightly controlled by visual experience. It has been found that the retina controls the axial eye growth rates depending on the amount and the sign of defocus imposed in the projected image. Glucagonergic amacrine cells were discovered that appear to encode for the sign of imposed defocus. It is not clear whether the downstream neurons, the retinal ganglion cells, still have access to this information-and whether i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
(99 reference statements)
4
15
0
Order By: Relevance
“…Some other members of this family have been localized in the vertebrate retina and several functions have been attributed to them [35, 36]. Glucagonergic amacrine cells represent a small subpopulation of the amacrine cells possibly playing a role in the visual processing [37, 38]. Other studies have shown that glucagon plays a role in eye bulb growth and glucagon is suggested to be an endogenous mediator of emmetropization [39].…”
Section: Resultsmentioning
confidence: 99%
“…Some other members of this family have been localized in the vertebrate retina and several functions have been attributed to them [35, 36]. Glucagonergic amacrine cells represent a small subpopulation of the amacrine cells possibly playing a role in the visual processing [37, 38]. Other studies have shown that glucagon plays a role in eye bulb growth and glucagon is suggested to be an endogenous mediator of emmetropization [39].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies reported VR values ranging from 1.5 c/deg for 1-to 25-day-old chicks [43] to about 7 c/deg for 6-month old birds [44]. Later Demello and collaborators [45] [47]. In this work averaged values of 6.7 and 5.6 c/deg were obtained at the area centralis for emmetropic and myopic eyes respectively.…”
Section: Discussionmentioning
confidence: 79%
“…This variability is also present when computing the behavioral spatial resolution in chicks, ranging between 1.5 c/deg reported by Over and Moore [54] and 6.0-8.6 c/deg measured by Schmid and Wildsoet [55], and Diedrich and Schaeffel [53]. Our estimates are similar to Ghim and Hodos’ data [52] and higher than those reported by Diedrich and Schaeffel [53]. No data on MARP for different retinal eccentricities have been found in the literature to establish a comparison.…”
Section: Discussionmentioning
confidence: 83%
“…Values ranged between 140 c/deg for the eagle [24], 18 c/deg in pigeon [51], 6 c/deg for the quail [52] and about 4 c/deg in chicken [53]. This variability is also present when computing the behavioral spatial resolution in chicks, ranging between 1.5 c/deg reported by Over and Moore [54] and 6.0-8.6 c/deg measured by Schmid and Wildsoet [55], and Diedrich and Schaeffel [53]. Our estimates are similar to Ghim and Hodos’ data [52] and higher than those reported by Diedrich and Schaeffel [53].…”
Section: Discussionmentioning
confidence: 99%